2023
DOI: 10.20867/thi.26.2
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Climate Transition in Tourism Destinations in Croatia

Abstract: Purpose – Developed urban destinations face problems such as uneven distribution of infrastructure, environmental degradation and pollution, increased energy demands, uneven distribution of water and food, lack of basic sanitation, etc. Scientists and experts are recognizing increasing problems and pressures related to urban tourism infrastructure (transportation, housing, water, electricity, and urban services), so destinations are increasingly opting for complete redesign, which involves high investment cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Hoteliers are aware of the importance of their environmental and social concerns and that by being more transparent and accountable about their impacts, they can achieve a better competitive position, achieve cost savings, improve strategic decision-making and benefit the community [46][47][48]. Apart from studies on non-financial information in the hospitality industry which showed an unsatisfactory level of quality, research has already been conducted on the importance of environmental reporting in the hospitality industry [49], the impact of environmental and social reporting on the financial performance of hotels [50], the design of green hotels, the minimisation of energy consumption and the use of technological innovation to achieve sustainability [51,52], water management [53] or waste management [54,55].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hoteliers are aware of the importance of their environmental and social concerns and that by being more transparent and accountable about their impacts, they can achieve a better competitive position, achieve cost savings, improve strategic decision-making and benefit the community [46][47][48]. Apart from studies on non-financial information in the hospitality industry which showed an unsatisfactory level of quality, research has already been conducted on the importance of environmental reporting in the hospitality industry [49], the impact of environmental and social reporting on the financial performance of hotels [50], the design of green hotels, the minimisation of energy consumption and the use of technological innovation to achieve sustainability [51,52], water management [53] or waste management [54,55].…”
Section: Literature Reviewmentioning
confidence: 99%